(Invited) Stoner Ferromagnetism in Two-Dimensional Materials. (3rd July 2019) - Houssa, Michel; Meng, Ruishen; Iordanidou, Konstantina; Pourtois, Geoffrey; Afanas'ev, Valery V.; Stesmans, Andre
Abstract : Hole-doping of GaX, InX (X=S or Se) and SnO monolayers is predicted to induce a stable ferromagnetic order in these two-dimensional materials, making them potentially interesting for nanoscaled spintronic devices. We discuss here results from first-principles simulations on the p-type doping induced Stoner ferromagnetism in these 2D materials. Hole doping, induced by intrinsic and extrinsic point defects is considered. Metal vacancies are found to produce shallow spin-polarized gap states near the valence band edge, leading to a p-type behavior. Among the investigated potential extrinsic defects (dopants), As substitution of the oxygen atoms in SnO or Bi substitution of the selenium atoms in InSe appears to be good candidates for the hole doping of these 2D materials.